Replication Data for: Acoustic occurrence of deep-diving cetaceans in the southern Adriatic Sea - Constaratas, Alexandra Nathalie; Holcer, Draško; Özgöbek, Özlem; Širović, Ana (DataverseNO, 2025)
Goose-beaked whale (Ziphius cavirostris) and sperm whale (Physeter macrocephalus) are two deep-diving odontocete species known to occur in the southern Adriatic Sea, based on intermittent stranding and sighting data. To get a better understanding of their presence in this region, we studied the occurrence of echolocation clicks produced by these species in passive acoustic recordings. Passive acoustic data were collected offshore Dubrovnik, Croatia. Data were collected from October 2018 to December 2019 and from June 2020 to December 2020 using a High-frequency Acoustic Recording Package (HARP) deployed at approximately 1,000 m depth. To determine the occurrence of echolocation clicks, a two-step process was used: automated detection followed by manual annotation of the detected clicks. Automated detection was implemented using a low signal-to-noise ratio threshold and a broad range of parameters to detect as many clicks as possible. Two click clustering algorithms were evaluated for performance on this data set: an unsupervised clustering algorithm and a filtering algorithm. The performance of the algorithms was compared to the manual annotations to determine a time-effective method for future monitoring. Both species were found to be acoustically active in the southern Adriatic Sea. Goose-beaked whales were detected throughout the recording period, with echolocation clicks peaking during the winter of 2018–2019 and in the spring of 2019. Conversely, sperm whales were more acoustically active during short, irregular windows, mostly during the summer of 2019. These results suggest that goose-beaked whales are residents, and, due to the irregularity of their detection, sperm whales are likely occasional visitors to this region. The unsupervised clustering algorithm performed better than the tested filtering algorithm, with F-scores of 0.74 and 0.46, respectively. This study provides knowledge that can help with effective conservation efforts and further contribute to our understanding of cetacean occurrence in ...